POSSIBILITIES OF THE CONTENT OF EDUCATION IN THE PROCESS FORMATION OF INTELLECTUAL SKILLS OF SENIOR STUDENTS - L.V. Lovyanova (Academy of Cognitive and Natural Sciences, 2022)
Corning from wording o f the notion "intellectual skills" and structures of the skills as complex larval formation in this article the didactic possibilities of the contents of the education and methodical methods o f its learning, which promote the most efficient shaping intellectual component personality of the graduate of the school are openedEmphases is spared realization problem approach to process of the shaping the intellectual skills o f the creative nature on example o f disciplines naturally-mathematical cycle.